Measurement of the top-quark mass in all-jets t(t)over-bar events in pp collisions at root s=7 TeV - Chatrchyan, S.; Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Bergauer, T.; Dragicevic, M.; Ero, J.; Fabjan, C.; Friedl, M.; Fruehwirth, R.; Ghete, V. M.; et al. (Springer, 2014)
The mass of the top quark is measured using a sample of t (t) over bar candidate events with at least six jets in the final state. The sample is selected from data collected with the CMS detector in pp collisions at root s = 7 TeV in 2011 and corresponds to an integrated luminosity of 3.54 fb(-1). The mass is reconstructed for each event employing a kinematic fit of the jets to a t (t) over bar hypothesis. The top-quark mass is measured to be 173.49 +/- 0.69 ( stat.) +/- 1.21 ( syst.) GeV. A combination with previously published measurements in other decay modes byCMSyields a mass of 173.54 +/- 0.33 (stat.) +/- 0.96 (syst.) GeV.